Вербицький і Лисенко: романтична візія українства у концептуальній символьності «Заповітів» - Кашаюк, Вікторія Миколаївна (Львівська національна музична академія імені М. В. Лисенка, 2004)
The presented scientific research examines the two earliest interpretations of the poetic heart of the Ukrainian mentality, symbolic in view of the names of the composers and the history of the premieres - these are "Testaments" by Mykhailo Verbytskyi and Mykola Lysenko, which reflect the two mental sides of Ukrainianness, and whose authors, together with T. Shevchenko, became the creators of the national romantic vision, which we are trying to grasp to this day. "Testament" has a special symbolic meaning for the work of the priest and composer M. Verbytskyi, almost the same age as T. Shevchenko, who created this musical canvas two years before his own death. The romantic cantata-poem for baritone, mixed and male choir with orchestra combines the traditions of D. Bortnyansky and the new, Western European trends, which can be seen in the advanced symphonic development from the extended introduction throughout the work. The conceptuality of M. Lysenko's "Testament" is revealed in the transmission of the author-poet's appeal ‒ "from the first person" ‒ to all of us. M. Lysenko places the concept of the work in a nationalspiritual context, combining the features of folk and spiritual types of singing, and in this we see a vivid example of the embodiment of supraindividual, ethically exalted, confessional pathos
Keywords: musical-poetic concept; T. Shevchenko's "Testament"; romantic style; narration; ethical message; national-spiritual context; музично-поетичний концепт; "Заповіт" Т. Шевченка; романтичний стиль; наратив; етичне послання; національно-духовний контекст